2016
DOI: 10.1111/iju.13104
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for acute kidney injury after radical cystectomy

Abstract: Abbreviations & Acronyms AKI = acute kidney injury AKIN = Acute Kidney Injury Network BMI = body mass index CI = confidence interval CVD = cardiovascular disease DM = diabetes mellitus eGFR = estimated glomerular filtration rate HT = hypertension IHD = ischemic heart disease KDIGO = Kidney Disease: Improving Global Outcomes NAC = neoadjuvant chemotherapy NSAID = non-steroidal antiinflammatory drugs OR = odds ratio POD = postoperative day RC = radical cystectomy RIFLE = Risk, Injury, Failure, Loss, End-Stage Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
(53 reference statements)
1
17
0
Order By: Relevance
“…We thank Jin et al 1 for their comment on our article. As they commented, the incidence of acute kidney injury (AKI) would increase when using serum creatinine adjusted by the fluid balance, which was proposed by Moore et al 2 However, we can see that the incidence of surgery-associated death, need for renal replacement therapy and length of stay…”
Section: Conflict Of Interestmentioning
confidence: 89%
See 1 more Smart Citation
“…We thank Jin et al 1 for their comment on our article. As they commented, the incidence of acute kidney injury (AKI) would increase when using serum creatinine adjusted by the fluid balance, which was proposed by Moore et al 2 However, we can see that the incidence of surgery-associated death, need for renal replacement therapy and length of stay…”
Section: Conflict Of Interestmentioning
confidence: 89%
“…In a retrospective study by Ikehata et al assessing the incidence, risk factors and impact on short-term outcomes of postoperative acute kidney injury (AKI) in patients undergoing radical cystectomy, they showed that hypertension, estimated glomerular filtration rate <60 mL/min/1.73 m 2 and neoadjuvant chemotherapy were independent risk factors for postoperative AKI. 1 However, postoperative AKI was not associated with prolonged hospital stay. Other than the limitations described by the authors in the Discussion, we noted that several issues of this study were not well addressed.…”
mentioning
confidence: 94%
“…As they commented, the incidence of acute kidney injury (AKI) would increase when using serum creatinine adjusted by the fluid balance, which was proposed by Moore et al . However, we can see that the incidence of surgery‐associated death, need for renal replacement therapy and length of stay in the intensive care unit after radical cystectomy (RC) were all significantly less than after cardiac surgery . Therefore, the diagnosis of AKI by using adjusted serum creatinine would be unlikely to affect short‐term postoperative clinical outcomes in the current study.…”
mentioning
confidence: 63%
“…However, numerous studies have demonstrated the relationship between renal function and patients' preoperative characteristics, comorbidities, and presence of hydronephrosis (2,4,5). Risk factors for early postoperative acute renal dysfunction have also been identified (6). However, there are no definitive data regarding the effects of postoperative renal function on post-RC complications (6) and oncologic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for early postoperative acute renal dysfunction have also been identified (6). However, there are no definitive data regarding the effects of postoperative renal function on post-RC complications (6) and oncologic outcomes. The aim of this study was to investigate the association between postoperative renal function and preoperative factors, post-RC oncologic outcomes, and complications.…”
Section: Introductionmentioning
confidence: 99%